Development of Autoantibodies Following BNT162b2 mRNA COVID-19 Vaccination and Their Association with Disease Flares in Adult Patients with Autoimmune Inflammatory Rheumatic Diseases (AIIRD) and the General Population: Results of 1-Year Prospective Follow-Up Study - Tal Gazitt; Tali Eviatar; Jacqueline Shear; Roni Meidan; Victoria Furer; Joy Feld; Amir Haddad; Muna Elias; Nizar Hijazi; Nili Stein; Pninit Shaked Mishan; Anna Zetser; et al. (Vaccines, 2023)
Development of autoantibodies following BNT162b2 mRNA COVID-19 vaccination and their association with disease flares in adult patients with autoimmune inflammatory rheumatic diseases (AIIRD) and the general population: results of 1-year prospective follow-up study. We conducted a prospective study aimed at investigating the incidence of appearance of autoantibodies (antinuclear, antiphospholipid, and rheumatoid factor) in the sera of 463 adult patients with AIIRD compared to 55 controls from the general population prior to, and following the second and third vaccine doses, and at 1-year of follow-up. Pre- and post-vaccination disease activity indices and the association of autoantibodies with rheumatic disease flares and new onset AIIRD were examined. Autoantibody development of any type in AIIRD patients vs. the controls was 4.0% (vs. 6.7%, p = 0.423) following two vaccine doses and 7.6% (vs. 0%, p = 0.152) after three doses. There was no significant difference in sex, age, or disease-type among individuals with and without autoantibody development, regardless of the immunosuppressant use. More patients developed autoantibodies following the third than the second vaccine dose (p = 0.004). Disease flares occurred in 5.8% and 7.2% of AIIRD patients following second and third vaccine doses, respectively, with autoantibody production increasing the risk of flares following the second (p = 0.002) and third (p = 0.004) vaccine doses. BNT162b2 vaccination resulted in the development of autoantibodies in a minority of AIIRD patients and controls. Autoantibody development was associated with disease flares in patients, but no new-onset autoimmunity was observed.